The Concept of Resolving the Conflict of Norms Between Criminal Confiscation and General Bankruptcy Confiscation of Bankruptcy Assets Viewed from the Perspective of Justice - Handayani, Suci Hati; Sambas, Nandang; Jamila, Lina (Journal La Sociale, 2024)
In the scope of business, business actors, both individuals and legal entities, often borrow money (debt) with the aim of obtaining capital intended for the continuity of their business activities. In practice, often a debtor fails to fulfil his obligations or achievements, not because it is caused by force majeure (overmatch). Such a situation is called default. In Bankruptcy Law, there is a type of confiscation, namely general confiscation. In connection with that, there is a conflict of norms between the provisions of general confiscation in Article 31 paragraph (2) of Law No. 37 of 2004 with the provisions of criminal confiscation / confiscation in Article 39 paragraph (2) of the Criminal Procedure Code. This research method uses normative juridical and empirical juridical approaches. The data used in legal research are primary data and secondary data. The results of this study, the Government as the Regulator is expected to immediately make a legal formulation policy in connection with the general confiscation of bankruptcy as regulated in Law No. 37 of 2004 and criminal confiscation as regulated in the Criminal Procedure Code and other related regulations, and in order to seek justice in law enforcement, especially related to confiscation of bankruptcy property, in essence the provisions of laws and regulations do not contradict each other, must be in harmony in order to ensure legal certainty and legal protection in its implementation. Therefore, it is necessary to revise the two confiscation provisions regulated in the two regulations, especially the general bankruptcy confiscation provisions regulated in Article 31 of Law No. 37 of 2004.